Adomian decomposition method for a stepped fin with all temperature-dependent modes of heat transfer. (March 2015) - Singla, Rohit K.; Das, Ranjan
Abstract: The application of Adomian decomposition method (ADM) is demonstrated for a nonlinear problem involving conductive, convective and radiative stepped fin with temperature-dependent parameters. The parameters which have been considered to be temperature-dependent are the thermal conductivity, the surface heat transfer coefficient and the emissivity. The performance of the stepped fin is compared with that of the straight fin. For validating the present method, the results obtained using ADM are compared with relevant results of the differential transformation method available in the literature. Effect of various thermo-physical parameters affecting the temperature and the efficiency are illustrated. Comparisons of performance parameters reveal that for a given set of conditions, the stepped fin performs better than the straight fin.